SIFAT FISIKOKIMIA SELAI NANAS LEMBARAN DENGAN VARIASI TEPUNG PORANG SEBAGAI PENSTABIL - Ashar, Muhammad Asri Bin; Efendi, Raswen; RSH, Ahmad Ibrahim (Universitas Riau, 2024)
Pineapple sheet jam products can provide value to pineapple fruit. This study aims to determine the concentration of porang flour as a stabilising agent in terms of physicochemical properties in making sheet jam. The research was conducted experimentally using a completely randomised design (CRD) with four treatments and four replications, resulting in 16 experimental units. The treatment was the addition of flour, namely TP1 (0.25g porang flour), TP2 (0.50g porang flour), TP3 (0.75g porang flour), and TP4 (1.00g porang flour). The parameters observed included moisture content, ash content, syneresis test, total soluble solids (TPT), crude fibre content, and sensory assessment consisting of descriptive test and hedonic test including colour, aroma, taste, elasticity, and overall assessment of jam sheets. The treatment chosen in this study was the TP3 treatment with 0.75g flour addition which had characteristics of 17.17% moisture content, 0.30% ash content, day 2, 3, and 4 syneresis test of 1.89%, 3.42%, and 4.28% respectively, total soluble solids (TPT) of 22.10°Brix, and crude fibre content of 0.05%.